(untitled) (Journal of Partial Differential Equations, 2020)
We prove the global existence of a unique mild solutions to the incompressible MHD equations when the initial data are less than the viscosity coefficients in a new critical space introduced by Lei and Lin [1]. Moreover, we prove that solutions decay to zero as time goes to infinity.